Mandioca minimamente processada submetida à radiação de acelerador de elétrons - Daiuto, Érica Regina [UNESP]; Vieites, Rogério Lopes [UNESP]; Carvalho, Lídia Raquel de [UNESP]; Russo, Viviane Citadini [UNESP]; Watanabe, Ligia Mouriguchi [UNESP]; Lozano, Mariana Gonçalves [UNESP]; Garcia, Márcia Regina [UNESP]; Morais, Maria Rosa de [UNESP] (My University, 2011)
Conservation fresh cassava and peeled can be done by use of packings in modified atmosphere and low temperature. Radiation is a physical method used in the conservation of foods, being the source of cobalt 60 (gamma radiation) already appraised in minimally processed products processed. Radiation use from electrons accelerator was not studied with this purpose. The aim of this work was to evaluate the quality of minimally processed cassava subjected to electrons accelerator radiation. For processing the cassava roots (IAC - 567-70) were used. After preparation, the roots were packed in expanded polystyrene (EPS) trays, covered by low densidy polyethylene (LDPE) plastic film, being subjected to electrons accelerator radiation in doses 0 (control), 0,48; 0,8; 1,12; 1,45 KGy. It was still obtained another treatment whose, roots were packed in nylon+ polyethylene with vacuous application. Packed roots of all treatments were stored under refrigeration (5 ± 1 ºC) and evaluations were made to the 0, 3, 6, 9 and 12 days. Evaluated analyses were: titrable acidity, pH, firmness, coloration, polyphenoloxidase activity enzyme, cooking time and roots hydration percentage. Evaluations just proceeded unt i l the n ine storage day , because after th is per iod roots a lready presented physiologic and microbiological alterations. Alterations were detected visually. For titrable acidity, the roots packed in vacuum obtained the smallest values, following by the control packed in trays. For the other treatments, values of acidity increase, tends this behavior influenced in the pH values that it went larger for these samples. For the other appraised parameters it didn't happen significant difference among treatments, but alterations were observed with the storage. Firmness decreased with the storage. Brightness values and yellow color component they decreased with the storage and the color values b * (green) they increased. Polyphenoloxidase activity enzyme was maximum in the day of elaboration of the product and it decreased with the storage. Cooking time and hydration percentage decreased with the roots storage. Difference was not observed among the treatments for appraised parameters, however visually it was detected microbiological alterations more intense in control sample and with smaller dosage of radiation.

A conservação da mandioca in’n atura e descascada pode ser feita mediante uso de embalagens em atmosfera modificada e baixa temperatura. A radiação é um método físico utilizado na conservação de alimentos, sendo a fonte de cobalto 60 (radiação gama) já avaliada em produtos minimamente processados. O uso de radiação por acelerador de elétrons não foi estudada com esta finalidade. O objetivo desta pesquisa foi avaliar a qualidade de mandioca minimamente processada (MMP) submetida radiação de acelerador de elétrons. Para o processamento mínimo foram utilizadas raízes de mandioca (IAC- 567-70) que após o preparo foram acondicionadas em embalagens de poliestireno expandido e revestidas por filme plástico de polietileno de baixa densidade (PEBD), sendo submetidas a radiação de acelerador de elétrons nas doses 0,0 (controle), 0,48; 0,8; 1,12; 1,45 KGy. Foi obtido ainda outro tratamento cujas, raízes foram acondicionadas em embalagem de nylon+polietileno com aplicação de vácuo. As raízes acondicionadas, de todos os tratamentos foram armazenadas sob refrigeração (5 ± 1 ºC) e as avaliações realizadas aos 0, 3, 6, 9 e 12. As análises realizadas foram: acidez titulável, pH, firmeza, coloração, atividade da enzima polifenoloxidase, tempo de cocção e porcentagem de hidratação das raízes. As avaliações seguiram apenas até o 9º dia de armazenamento, pois após este período as raízes já apresentavam visualmente alterações fisiológicas e microbiológicas. Exceto para o pH, não foi verificada diferença entre os tratamentos das MMP. Observou-se aumento dos valores de acidez ao longo dos dias de armazenamento. Os valores de luminosidade e componente de cor amarela (cor a*) diminuíram com o armazenamento e os valores de cor b* (verde) aumentaram. Para firmeza observou-se um aumento dos valores entre os 3 e 6º dia de armazenamento, diminuindo a partir deste momento. A atividade da enzima polifenoloxidase foi maior no dia da elaboração do produto. O tempo de cocção e porcentagem de hidratação diminuíram com o armazenamento. Não foi observada diferença entre os tratamentos das MMP para os parâmetros avaliados, no entanto, visualmente foi detectada alteração microbiológica mais intensa nas amostras controle e naquelas com baixa dose de radiação.
Minimally processed cassava subjected to electrons accelerator radiation
Keywords: Manihot esculenta CRANTZ; Polyphenoloxidase; Cooking time; Color; Manihot esculenta CRANTZ; Tempo de cocção; Polifenoloxidase; Cor